IAHPSTC Exchange Program - Feedback of the pilot project in Summer 2009 - Lamb, T.; Roseboom, G. W.; Pelkonen, J.; Lahtinen, J. (6. Forum on Elite Sport- IAHPSTC, Colorado Springs, USA, 9.-13. September 2009, 2009)
OTC Chula Vista, USA; OTC Colorado USA; HPC Vuokatti, Finland; CAR Sierra Nevada, Spain